Pre-Feasibility Project for the Creation of a High-Traffic Pavers Factory for the Decentralized Autonomous Government of Sigchos Canton (Journal of Civil Engineering Researchers, 2024)
The objective of this study is to determine the technical, legal, and economic feasibility of establishing a heavy-duty paver block factory for the Municipal Decentralized Autonomous Government of Sigchos Canton. The methodology used included a non-experimental research approach, with an explanatory, descriptive, and correlational design. Surveys were conducted with the legal representatives of the parish councils to gather primary information, while secondary information was obtained through bibliographic and documentary review. The results from the market study reveal significant demand and acceptance from the parish representatives toward the production of vehicular pavers, supporting the need to improve local road infrastructure and economic development. A market opportunity was identified both in government projects and private initiatives, with an estimated daily demand of 2,800 paver units. As for the technical study, efficient production processes were designed, with rigorous quality control measures and an annual production capacity of 2,880,000 pavers. The administrative-legal analysis reflects a comprehensive and proactive approach to meeting legal and regulatory requirements, including the decision to establish a Corporation (S.A.) and obtaining the necessary permits for the factory’s operation. Finally, the financial study results indicate that the project is economically viable, with a positive Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), average profitability (AP), and Benefit-Cost Ratio (BCR), supporting the project's feasibility.
Keywords: Economic Feasibility; Paver block factory; Municipal Decentralized; Autonomous Government of Sigchos Canton; Technical legal